THE MOMENTUM THEORY OF GOODWILL. - Nelson, Robert H. (The Accounting Review, 1953)
The purpose of this article is to analyze purchased goodwill with a view to seeing whether it ought to be amortized by charges to income, and in general to present a case for amortization. Goodwill refers to favorable attitudes toward an enterprise. Thus, it includes the favorable attitudes of customers, employees, credit grantors, investors, suppliers, governmental regulators, politicians and the general public. Other descriptive terms for goodwill are reputation and customer habit. Usually goodwill is transferred only on the sale of the entire concern. However, there are cases where the goodwill involved in a patent, copyright, secret process, or trademark is transferred with the patent or other item without selling the entire business. Goodwill may fade from memory unless the reputation is fed or replenished by new feats or reminders. Reputations fade from memory unless the reputation is fed or replenished by new feats or reminders. Goodwill is hard to build up, so the buyer of a concern will often pay a large sum of money for the goodwill.